Leveraging Artificial Intelligence: Applications To Enhance Learning Experiences In Higher Education: Transforming Pedagogical Practices For The 21st Century - Sobia Tasneem, Saeed Shakir, Fariha Sohil, Muhammad Umair Sohail, Ali Asgher, Mr. Abdul Jabbar (Migration Letters, 2024)
Teaching and learning, changed by electronic technology, are the foundations of contemporary education. The introduction of innovative technologies (e.g., artificial intelligence, virtual reality, and adaptive learning systems) altered the classic classroom environment . The objectives of the study were; (1) What are impacts of emerging techniques AI, virtual reality and adaptive learning on learner engagement, critical thinking skills and knowledge retention in education in 21st century? (2) What were the various applications for integrating technology in designing curriculum efficiently with personalized student-centered learning agile methodologies? (3) How do university teachers see about using emerging educational elements? All the male and female teachers and students of the National University of Modern Languages (NUML) Multan constituted the population. A total number of 15 university teachers and 70 students were taken with a self-devised questionnaire developed for data collection . used random sampling techniques for this sample. The analysis techniques utilized SPSS version 21, and calculation of frequency, percentage, mean scores, and standard deviation using t-tests for independent samples were done to measure the results of the study. With these technological tools, learning environments became even more individualized, interactive, and student-oriented. The research focused on the latest improvements in educational technologies and how it affects learner interest, critical thinking, and remembering knowledge. This study also addressed challenges related to digital equity and teacher training in adopting these tools, offering insights into best practices for overcoming barriers. According to the study, innovative technologies had significant potential to improve educational outcomes and experiences through strategic use of technology, equipping students for their future in a digital world.